2004
DOI: 10.1038/sj.gt.3302309
|View full text |Cite
|
Sign up to set email alerts
|

Self-inactivating retroviral vectors with improved RNA processing

Abstract: Three RNA features have been identified that elevate retroviral transgene expression: an intron in the 5 0 untranslated region (5 0 UTR), the absence of aberrant translational start codons and the presence of the post-transcriptional regulatory element (PRE) of the woodchuck hepatitis virus in the 3 0 UTR. To include such elements into self-inactivating (SIN) vectors with potentially improved safety, we excised the strong retroviral promoter from the U3 region of the 3 0 long terminal repeat (LTR) and inserted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 48 publications
(68 reference statements)
1
59
0
1
Order By: Relevance
“…15,16 However, several types of murine leukemia virus g-retroviral SIN vectors were reported to yield lower viral vector titers, depending on the vector context. 17,18 This has been associated to an abundant transcription from the internal promoter driving transgene expression, which may occur at the expense of full-length viral RNA transcription originating from the LTR in packaging cells. 18,19 Various approaches were taken to overcome these limitations, such as the introduction of the post-transcriptional element from Woodchuck hepatitis virus into the 3¢-untranslated region of SIN vectors, 20,17 or the incorporation of upstream polyadenylation enhancer elements derived from viral or cellular genes into the 3¢U3 region of the LTR, allowing partial recovery of high viral vector titers.…”
Section: Retroviral Vectors Represent An Important Tool In Human Genementioning
confidence: 99%
“…15,16 However, several types of murine leukemia virus g-retroviral SIN vectors were reported to yield lower viral vector titers, depending on the vector context. 17,18 This has been associated to an abundant transcription from the internal promoter driving transgene expression, which may occur at the expense of full-length viral RNA transcription originating from the LTR in packaging cells. 18,19 Various approaches were taken to overcome these limitations, such as the introduction of the post-transcriptional element from Woodchuck hepatitis virus into the 3¢-untranslated region of SIN vectors, 20,17 or the incorporation of upstream polyadenylation enhancer elements derived from viral or cellular genes into the 3¢U3 region of the LTR, allowing partial recovery of high viral vector titers.…”
Section: Retroviral Vectors Represent An Important Tool In Human Genementioning
confidence: 99%
“…Finally, when constructing a new generation of retroviral self-inactivating vectors, we placed the internal promoter 18 bp downstream of the PBS and thus 24 bp upstream of the 5Јss. In this configuration, we observed complete splicing of the retroviral intron, strongly suggesting that sequences located upstream of the promoter insertion site (comprising the second half of R, U5, and 18 bp 3Ј of the PBS) negatively regulate gammaretroviral splicing (16).…”
Section: Discussionmentioning
confidence: 84%
“…Although the infectious titer was reduced by about 1 order of magnitude, unspliced genomic RNA was still formed, arguing for the existence of additional splice inhibitory sequences. Recently, we have observed that self-inactivating MLV vectors display complete splicing of the retroviral intron when the promoter was placed in between the primer binding site (PBS) and the 5Јss (16). Using a number of mutants, we here demonstrate that distinct sequence elements upstream of the 5Јss either promote or inhibit splicing.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…This could be achieved using safety-modified vectors self-inactivating (SIN) LTR, derived from either HIV, 40,41 Foamy virus 42,43 or MLV. [44][45][46] In summary, the present study shows that mbC46, either alone or in combination with MGMT-P140K, can be retrovirally introduced into murine HSCs and expressed at high levels in their multilineage progeny, without gross alterations of hematopoiesis. This encourages further studies to evaluate the safest procedures that ensure high levels of chimerism in vivo, and coexpression with additional anti-HIV genes and/or selectable marker genes.…”
Section: Stem Cell-mediated Inhibition Of Hiv Entry a Schambach Et Almentioning
confidence: 98%